Cross-Shaped Leadership: On the Rough and Tumble of Parish Practice - Berntsen, John A. (Rowman & Littlefield Publishers, 2008)
For Lutheran pastor John Berntsen, the cross is about more than the crucifixion on Good Friday. It is shorthand for the whole drama of salvation--God's decisive act of reconciling the world to God's own self. The cross is dying and rising with Christ, but at a deeper level it is the story of the world's resistance to grace. Those who lead are subject to the cross no less than others. In contrast with the current fashion for "visionary" or "purpose-driven" leaders, cross-shaped leaders are not primarily the providers of master plans, nor are they master builders. Cross-shaped leadership is provisional, contextual, and fallible--open-ended ministry that has the character of a pilot project. It is always under construction and revision. Our moment-by-moment functioning in ministry is subject to countless deaths and resurrections, few of which are heroic or glorious. But Berntsen offers good news within this potentially dismal perspective. He writes, "Once we've accepted the truth that ministry is hard, even impossible--once we've stopped living in denial of this reality, or perhaps whining about it--it becomes the truth that sets us free. We cease being gloomy servants, weighed down by our resentful conviction that we are all alone in our work--the closet atheism born of the worry, 'If I don t do it, nobody will'--and instead become joyful coworkers of a strong, wise, and consoling Lord." With optimism, humor, and deep empathy, Berntsen's Cross-Shaped Leadership offers hope and challenge in the midst of the rough and tumble of parish practice.